PELATIHAN TEKNOLOGI PENGOLAHAN PAKAN KOMPLIT BERBASIS GREEN PROTEIN LOKAL SERTA MANAJEMEN AGRIBISNIS UNTUK MENINGKATKAN PRODUKTIVITAS SUSU KAMBING - Sukarne; Sutaryono, Yusuf Akhyar; Fahrullah; Nursan, Muhammad (Universitas Mataram, 2024)
This service program is motivated by the abundance of local forage sources from legume types which have great potential to be created into feed for milk-producing goats. On the other hand, the low supply of nutrition in rural communities is an important issue causing stunting. In fact, it is understood that goat's milk has great potential as a source of animal protein for society. This service aims to provide assistance (technology transfer) for complete, nutrient-rich green protein-based feed which is highly available in Lombok, such as turi plants, lamtoro plants, moringa plants and pineapple skin waste which has great potential. The next goal is to organize agribusiness management which still appears to be not running optimally. Starting from team management to production management. The method for implementing this service includes the Participatory Rural Appraisal (PRA) method by making CRF a place for providing assistance in implementing complete feed and involving communities who are CV partners. CRF as many as 20 people to benefit from the program. The activity stages include the preparation, implementation and evaluation stages of the activity. The results of service activities show that there has been an increase in community knowledge and skills in understanding and making complete feed to increase goat milk productivity. Based on the results of feed experiments on goats, data was also obtained on an increase of 200 ml/head (previously only 500 ml/head increased to 700ml/head). Knowledge and skills regarding more effective and efficient management of dairy goat agribusiness will increase after participating in community service activities.